Behavior Intention to Use Online Zakat: Application of Technology Acceptance Model with Development - Purwanto, Purwanto; Sulthon, Muhammad; Wafirah, Milna (ZISWAF, 2021)
Indonesia is one of the countries with the largest Muslim population in the world, but the level of zakat is not too heavy. This can be seen from the low amount of zakat that has been successful compared to the potential for zakat. Seeing this fact, the Zakat Management Organization (OPZ) implements a digitalization strategy in collecting zakat funds, including in Magelang Regency. In order to understand the intention of the muzakki in paying zakat online, this study was conducted. This study uses the Technology Acceptance Model (TAM) theoretical framework by adding a moderating variable to electronic word of mouth (eWOM). This study was conducted using a quantitative approach with 135 respondents. The data were randomly collected using the internet (online). Data analysis used Structural Equation Modeling (SEM) Partial Least Square (PLS). The findings of this study suggest that attitudes can be expressed by perceived ease of use (PEoU), perceived usefulness (PU), and electronic word of mouth (e-WoM). Meanwhile, behavioral intention in this study proved to be reliable by electronic word of mouth (e-WoM) and attitude. The results of the moderation effect test prove that electronic word of mouth (e-WoM) in this study weakens the relationship between perceived ease of use (PEoU) and attitude. Electronic word of mouth (e-WoM) can assess the relationship of benefit (PU) to attitudes and behavioral intentions